An improved fuzzy fractal dimension for texture analysis - Al-Saidi, Nadia Mohammed Ghanim; Md. Said, Mohamad Rushdan; Abdulaal, Wael J. (WSEAS Press, 2015)
In the real life, a lot of phenomena cannot be described by the traditional geometry; fractals are one of these objects. It serves to give a suitable description for these objects. Texture analysis plays an important role in image processing. Fractal dimension is utilized in texture segmentation and classification and prove to be an interesting parameter to characterize image roughness and extract image feature. In some complex and irregular scenes, it becomes not effective for feature extracting and classification. Therefore, a more general approach known as fuzzy fractal dimension can be used to model such types of scenes effectively. A new fuzzy fractal dimension method is proposed in this paper, it is verified by the experiment on a set of nature texture images to show its efficiency and accuracy, a satisfactory result is found. It also offers promising performance when it is tested among some types of noises to show a good robustness to them.